The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ultsonch.2021.105792
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ultrasonic de-agglomeration of oxides through in-situ high-speed observations and acoustic measurements

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Interestingly, the eventual breakage of floating crystals occurs by the same fatigue failure from repetitive shock wave impacts as in the case of fixed crystals [22] . However, the fragmentation, refinement and dispersion of such particulates can also be realised through the mechanism of cavitation-induced microjetting and de-agglomeration [61] and remains a subject for further research. The high-speed images ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the eventual breakage of floating crystals occurs by the same fatigue failure from repetitive shock wave impacts as in the case of fixed crystals [22] . However, the fragmentation, refinement and dispersion of such particulates can also be realised through the mechanism of cavitation-induced microjetting and de-agglomeration [61] and remains a subject for further research. The high-speed images ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of bubble burst and acoustic streaming result in the dispersion of ultrafine particles in the molten metal. [23][24][25][26][27][28] For such a cavitation-aided implosion to occur in liquid metals, minimum ultrasonic intensity may lie between 80 and 100 W cm À2 . [29][30][31] It was experimentally demonstrated that the cavitation threshold pressure was reduced from 800 to 550 kPa with the increase in impurity concentration (i.e., alumina) from 0.005 to 0.1 wt% in an aluminum melt.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [3,9,10], USP was applied to melts already inoculated with TiB 2 , and some additional grain refinement was demonstrated as a result of TiB 2 de-agglomeration and dispersion. However, de-agglomeration requires longer processing times due to the complexity of mechanisms recently revealed [8]. Instead, here we used additional alloying with Zr as an indicator of cavitation-induced grain refinement.…”
Section: Resultsmentioning
confidence: 99%
“…The interest in USP has increased in the beginning of the 21 st century, giving rise to in-depth research into the related cavitation-driven mechanisms, as well as to examining various schemes and regimes of USP, also applicable to DC casting. On the fundamental level the mechanisms of cavitation-assisted nucleation on oxides, fragmentation of solid phases, and de-agglomeration of solid particles have been well established [4][5][6][7][8]. Also the acoustic parameters of USP, including the distribution of acoustic pressure in the melt, the effects of ultrasonic power, acoustic flows and shock waves, have been studied in detail and incorporated in numerical models [9][10][11].…”
Section: Introductionmentioning
confidence: 99%